Pengaruh Kecerdasan Emosi terhadap Kinerja pada Pegawai di Lembaga Pemasyarakatan Kelas IIA Bekasi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to determine the influence of emotional intelligence on employe performance at Bekasi Class IIA Penitentiary. The background of this research is based on the importance of employes' ability to manage and utilize emotions effectively to support work effectiveness in an environment with high levels of pressure and complexity, such as correctional institutions. This research uses a quantitative approach with a causal associative research design. The population in this study consists of all employes at Bekasi Class IIA Penitentiary, with a sampling technique using saturated sampling, resulting in a total of 106 respondents. The data analysis technique used is simple linear regression analysis, which was preceded by validity, reliability, and normality tests. The research results indicate that emotional intelligence has a positive and significant effect on employe performance. This means that the higher the level of emotional intelligence possessed by employes, the better their performance. The coefficient of determination (R²) indicates that emotional intelligence contributes 53.0% to employe performance, while the remaining percentage is influenced by factors outside the variables studied. Thus, emotional intelligence is an important factor that needs to be developed thru continuous training and coaching, in order to improve overall performance and the quality of correctional services.